Herzberg’s Motivation-Hygiene Theory and Employee Retention : Evidence from the IT & ITES Industry - Joseph, Ashima; Linge, Ashish A.; Muley, Anand (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present study aimed to evaluate the impact of “motivators and hygiene factors” (mentioned in Herzberg’s theory of workplace motivation) on the job satisfaction of the employees working in the Information Technology (IT) industry in Nagpur, MH, India. The researchers also wished to understand whether the “job satisfaction” of the employees influenced their retention in the company. Methodology : A sample survey of 1,019 employees working in IT and ITES companies in Nagpur was conducted. Analysis was performed using structural equation modeling and multiple regression techniques using SmartPLS and SPSS software. Purposive and snowball sampling techniques were used to select the respondents. Findings : Motivating and hygiene factors were found to have positive and significant impacts on the job satisfaction of IT professionals. Moreover, job satisfaction also impacted employee retention positively and significantly. The results revealed that hygiene factors affected job satisfaction more than motivating factors. Practical Implications : This research has significant implications for professionals and human resource managers working in IT companies. They obtained useful and scientific information on the factors affecting the job satisfaction of employees. The results helped them plan, devise, and revise their employee retention strategies. Originality : Unlike prior research on “Herzberg’s theory,” the present work evaluated the impact of “motivators and hygiene factors” on “job satisfaction” and “employee retention” in the IT & ITES industry in Nagpur, India.